2007
DOI: 10.1002/fld.1565
|View full text |Cite
|
Sign up to set email alerts
|

A divergence‐free interpolation scheme for the immersed boundary method

Abstract: SUMMARYThe immersed boundary approach for the modeling of complex geometries in incompressible flows is examined critically from the perspective of satisfying boundary conditions and mass conservation. It is shown that the system of discretized equations for mass and momentum can be inconsistent, if the velocity is used in defining the force density to satisfy the boundary conditions. As a result, the velocity is generally not divergence free and the pressure at locations in the vicinity of the immersed bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Thus, strict conservation of quantities such as mass, momentum or kinetic energy is not observed near the irregular boundary. The most severe manifestations of these shortcomings is the occurrence of non-divergence free velocities or unphysical oscillations of the pressure in the vicinity of the immersed boundary [43,30]. Numerous revisions of these interpolations are still proposed for improving the accuracy and consistency of this class of IB methods [30,3,49,43].…”
Section: Introductionmentioning
confidence: 98%
“…Thus, strict conservation of quantities such as mass, momentum or kinetic energy is not observed near the irregular boundary. The most severe manifestations of these shortcomings is the occurrence of non-divergence free velocities or unphysical oscillations of the pressure in the vicinity of the immersed boundary [43,30]. Numerous revisions of these interpolations are still proposed for improving the accuracy and consistency of this class of IB methods [30,3,49,43].…”
Section: Introductionmentioning
confidence: 98%
“…The coupling of momentum forcing methods with projection schemes introduces difficulties in imposing at the same time level the contuinity equation and the boundary conditions on the immersed interface (see [9] for example). The incompressibility of the flow may even be violated in the vicinity of the immersed boundary [10]. This may result in serious diffulties when computing boundary layers at high Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…A well known issue with this class of algorithms is their tendency to introduce large non-physical pressure oscillations (see [8] for example). Muldoon [9] even showed that the pressure could locally increase without bound as the time step goes to zero. These oscillations are caused by the lack of smoothness of the velocity across the boundary before the projection step [10].…”
Section: Introductionmentioning
confidence: 99%